Iron status of school children with varying intensities of Trichuris Trichiura infection - Ramdath, Dan D.; Simeon, D. T.; Wong, M. S.; Grantham-McGregor, S. M. (My University, 1995)
The relationship between varying intensities of Trichuris Trichiura infection and iron status was examined in Jamaican students, aged 7-11 years. A total of 409 children were identified with T. trichiura (epg greater than 1200.) A control group comprised 207 uninfected children who were matched by school and class to every pair of infected subjects. Blood samples were obtained from 421 children: 264 infected and 157 controls. Compared to the rest of children, those with heavy infections (epg greater than 10,000) had significantly lower Hb (11.5 +/ -1.3 vs 12.1 +/ -1.1g/dl), MCV (78.6 +/ -6.3 vs 81.2 +/ -5.5fl), MCH (28.2 +/ -2.9 vs 27.5 +/ -2.5pg), and MCHC (33.2 +/ -1.5 vs 33.9+/-1.4g/dl). Similarly, the presence of anaemia (Hb less than 11.0 g/dl) amongst heavily infected children (33 percent) was significantly higher than the rest of the sample (11 percent). These differences remained significant after controlling for confounding variables, including socio-economic status, age, gender, area of residence, and the presence of Ascaris infections. Differences in red cell count, ferritin, and free erythrocyte protoporphyrin were not statistically significant, and showed no association with the infectious load. These results suggest that in the Jamaican children studied, iron deficiency anaemia is associated with Trichuris infections over 10,000 epg but not with less infections.
DOI: 10.1017/S0031182000080938
Keywords: Infectious diseases